2021
DOI: 10.5472/marumj.866658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different respiratory samples and saliva for the detection of SARS-CoV-2 RNA

Abstract: Objective: We aimed to analyse the positivity rate and cycle threshold values indicating viral loads for SARS CoV-2 among different respiratory specimens and also to evaluate the diagnostic efficacy of saliva samples. Materials and Methods: We included combined oropharyngeal and nasopharyngeal swab (cONS), sputum, and tracheal aspirate (TA) specimens of patients. Unpreserved saliva samples were collected prospectively from hospitalized patients within 72 hours of admission. SARS CoV-2 RNA was extracted by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The reason for negative results is the sensitivity of saliva samples. In a study using the same kit as ours, SARS-CoV-2 RNA positivity in the saliva samples of COVID-19 patients was found at the level of 60%, 39 and it was 70% in another study performed with a different kit. 40 The fact that 80% of the samples were positive in our study shows that the sample quality was good.…”
Section: Limitationssupporting
confidence: 47%
“…The reason for negative results is the sensitivity of saliva samples. In a study using the same kit as ours, SARS-CoV-2 RNA positivity in the saliva samples of COVID-19 patients was found at the level of 60%, 39 and it was 70% in another study performed with a different kit. 40 The fact that 80% of the samples were positive in our study shows that the sample quality was good.…”
Section: Limitationssupporting
confidence: 47%
“…A few studies collect samples in RNA-stabilizing buffers, 16-19 but most collect dry-swabs or saliva in sterile collection vessels. 15,20-31 Without an RNA-stabilizing buffer, there is some risk of viral degradation during transport and handling. Moreover, most studies do not report quantitative analysis of viral loads, making it more difficult to interpret the observed results relative to the LOD values of the particular test used.…”
Section: Introductionmentioning
confidence: 99%
“…Considering only the pure (not induced or enhanced) saliva without the use of transport media to achieve the aim of this SS collection method, there are only four studies to compare. Three studies showed moderate [44] to strong [35], [36] agreement with one study showed weak [45] agreement. Note that from these four studies, only one study [35] included asymptomatic cases and still showed strong agreement.…”
Section: Diagnostic Agreement Comparison Between Ss and Tssmentioning
confidence: 86%
“…All studies were comparing the diagnostic value of SS SARS-CoV-2 RT-PCR results with any forms of TSS (NPS, OPS, and/or NOS). Several studies were also comparing SARS-CoV-2 RT-PCR results from other respiratory tract specimens such as tracheal aspirate and sputum [45], cerumen and tears [34], and nasal swabs [47], [48] in additions to SS.…”
Section: Participants and Study Characteristicsmentioning
confidence: 99%